Mental causation is not counterfactual: A defense of the exclusion argument against counterfactual solutions - Han, Sanghun. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
The modern debate in philosophy of mind revolves around reductive and nonreductive physicalism. Especially the reducibility of the mental to the physical has been one of the central issues in the debate. The so-called exclusion argument put forward by Jaegwon Kim is thought to raise grave challenges to nonreductive physicalism, for it shows that the theses of nonreductive physicalism are incoherent. As a response, some nonreductive physicalists have attempted to refute the argument by way of counterfactual analysis. More specifically, those counterfactual solutions are to falsify one of the core assumptions of the exclusion argument, viz., overdetermination. In this study, it is argued that the counterfactual solutions are not successful given that the mental and the physical are tied by a special sort of relation, namely, supervenience. To this end, three arguments are presented: (1) the counterfactual solutions give rise to semantic emptiness as to counterfactual talks. (2) the counterfactual solutions actually entail a certain version of the exclusion argument. (3) the counterfactual solutions wrongly interpret supervenience as a causal relation. The conclusion is drawn that the defense of the exclusion argument against the counterfactual solutions give some plausible reasons why reductive physicalism is a more viable option, and that instead of the dependence view of causation, the production view of causation seems to be a better candidate when it comes to the relation between the mental and the physical.
Keywords: Mental discipline.